2013
DOI: 10.17305/bjbms.2013.2389
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and antioxidant effects of buckwheat leaf and flower mixture in hyperlipidemic rats

Abstract: As a source of biologically active compounds, buckwheat has beneficial effects in nutrition due to its high content of flavonoids, particularly rutin. Aim of our study was to examine effects of buckwheat on plasma lipid status and phospholipids fatty acids composition, histological and parameters of oxidative stress in Wistar rats fed a high-fat diet. This study showed that buckwheat leaf and flower (BLF) mixture supplementation significantly reduce weight gain, plasma lipid concentrations and atherogenic inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In our previous supplementation trials on BLF by decreasing the percentage of palmitic acid and total SFA and increasing stearic acid and total PUFA improved FAs profi les in rat plasma, demonstrating an overall hypolipidemic effect in hyperlipidemic rats [10].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our previous supplementation trials on BLF by decreasing the percentage of palmitic acid and total SFA and increasing stearic acid and total PUFA improved FAs profi les in rat plasma, demonstrating an overall hypolipidemic effect in hyperlipidemic rats [10].…”
Section: Discussionmentioning
confidence: 77%
“…These effects were accompanied with improvement of FAs profi les of plasma phospholipids where supplementation with BLF signifi cantly decreased the percentage of palmitic acid and total saturated fatty acids (SFA) and increased the percentage of stearic acid and total PUFA [10]. To our knowledge, no reports are available assessing buckwheat effects on fatty acids in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced levels of C2 GPx and C2 CAT activities were the effect of raised and overwhelming levels of ROS (El-Demerdash et al, 2005;Avti et al, 2006); ROS has inhibitory effect on ROS scavenging enzymes such as CAT and GPx activities (Hassan and Fridovich, 1978;Avti et al, 2006). Consequently, raised levels of cytotoxic ROS engendered membrane lipid peroxidation with the production of associated by-products such as malondialdehyde (MDA) and 4-hydroxyalkenals (4HNE) (Shaker et al, 2010;Al-Dosari, 2011;Đurendić-Brenesel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Buckwheat (Fagopyrum esculentum) (Đurendić-Brenesel et al, 2013), Ocimum sanctum L. (Suanarunsawat et al, 2011) and Roselle (Hibiscus sabdariffa Linn) (Ochani and D'Mello, 2009) share similar antioxidant phytochemical profile with A. sativa extract (Ibegbulem and Chikezie, 2013). Accordingly, the presence of phytochemicals such phenolics, tannins and flavonoids in A. sativa extract, coupled with high content of antioxidant elementselenium (http.//www.completeherbal.com/details/garlic.htm; Banerjee and Maulik, 2002) contributed to the antioxidant property ofA.sativa extract.…”
Section: Discussionmentioning
confidence: 99%
“…Đurendić‐Brenesel et al examined the effects of buckwheat leaf and flower on plasma lipid status and phospholipid fatty acid composition, histology and parameters of oxidative stress in Wistar rats fed a high‐fat diet . The study showed that buckwheat leaf and flower mixture supplementation significantly reduced weight gain, plasma lipid concentrations and atherogenic index in rats fed a high‐fat diet.…”
Section: Other Buckwheat Productsmentioning
confidence: 99%